[(x-y)^7]÷(y-x)³-[4(x-y)²]²
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/07 01:41:24
[(x-y)^7]÷(y-x)³-[4(x-y)²]²[(x-y)^7]÷(y-x)³-[4(x-y)²]²[(x-y)^7]÷(y-x)&
[(x-y)^7]÷(y-x)³-[4(x-y)²]²
[(x-y)^7]÷(y-x)³-[4(x-y)²]²
[(x-y)^7]÷(y-x)³-[4(x-y)²]²
[(x-y)^7]÷(y-x)³-[4(x-y)²]²
=[(x-y)^7]÷[-(x-y)³-16(x-y)^4
=-(x-y)^4-16(x-y)^4
=-17(x-y)^4
原式=(x-y)^7÷[-(x-y)^3]-16(x-y)^^4
=-(x-y)^4-16(x-y)^4
=-15(x-y)^4
(y-x)³=-(x-y)³
则
[(x-y)^7]÷(y-x)³=-(x-y)^4
而[4(x-y)²]²=16(x-y)^4
则[(x-y)^7]÷(y-x)³-[4(x-y)²]²=-(x-y)^4-16(x-y)^4=-17(x-y)^4